Synthesis of the tetracyclic core of Illicium sesquiterpenes using an organocatalyzed asymmetric Robinson annulation - Trzoss, Lynnie; Xu, Jing; Lacoske, Michelle H.; Theodorakis, Emmanuel A. (Beilstein Journal of Organic Chemistry, 2013)
An enantioselective synthesis of the core framework of neurotrophic Illicium majucin-type sesquiterpenes is described here. This strategy is based on an organocatalyzed asymmetric Robinson annulation and provides an efficient approach for a diversity-oriented synthesis of Illicium natural products that holds remarkable therapeutic potential for neurodegenerative diseases.
Keywords: natural products; neurodegenerative diseases; neurotrophic small molecule; organocatalysis; total synthesis